(untitled) (Journal of Dentistry and Allied Science, 2025)
Background: Orbital fractures account for 40% of craniomaxillofacial injuries; of the four walls of the orbit, the floor, which is extremely thin, is the most frequently injured. According to the pertinent literature, such fractures represent 67 to 84% of cases of orbital fractures (Sharma et al. 2012). Injuries in the orbital region have profound functional as well as aesthetic implications. Management of orbital fractures remains one of the most controversial issues in maxillofacial trauma with regard to the classification, diagnosis, surgical approach and treatment. Objectives To evaluate and compare the aesthetic outcome of two most commonly applied approaches the transconjunctival with lateral canthotomy and the subciliary approach for the treatment of infraorbital rim and orbital floor fractures. Method 20 patients with infraorbital rim and orbital floor fractures were treated by transconjunctival and subciliary approaches 10 in each group. 20 patients with a follow-up of 1st, 3rd and 6th post-operative week were included in the study. In post-operative period surgeon evaluated the cosmetic result of the procedure. Result On 6th post-operative week 100% patient of subciliary group showed visible scar which is statistically significant. In this group 40% patient showed transient ectropion which is statistically significant. In transconjuctival group no visible scar was seen. Only 30% patient showed transient entropion which is not statistically significant. Conclusion The transconjunctival incision produce better aesthetic result than subciliary incision. Journal of Dentistry and Allied Science, Vol. 7 No 2: 19-25